Application of Threshold Concepts in Natural Resource Decision Making - Guntenspergen, Glenn R. (Springer New York : Imprint: Springer, 2014)
Scientists and managers have largely abandoned classic models that assume natural systems are in equilibrium and recognize the importance of understanding interactions between, and among, biotic and abiotic factors in ecosystems, and how these interactions lead to complexities that should be factored into natural resource management decisions. Even though the existence of ecological thresholds is becoming increasingly apparent, this has not been followed by its widespread adoption and incorporation into management decisions and goals. The ability to move from theory to application and make threshold concepts a problem solving tool for natural resource management remains a daunting challenge. This book addresses this challenge and shows how threshold concepts can be integrated into conservation and land management decision making.